2017
DOI: 10.2147/clep.s128627
|View full text |Cite
|
Sign up to set email alerts
|

The association between thyroid disorders and incident gout: population-based case–control study

Abstract: ContextThyroid hormones influence kidney function and thereby might alter serum urate levels, a major risk factor for gouty arthritis.ObjectiveTo assess the risk of developing incident gout in association with hypothyroidism or hyperthyroidism.DesignRetrospective population-based case–control analysis.SettingUK-based Clinical Practice Research Datalink, a primary care research database.PatientsWe identified adult patients with a diagnosis of incident gout between 1990 and 2014. We matched one control to each g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…The association between hypothyroidism and hyperuricemia (an important risk factor for the development of gout) has been firmly established. [35][36][37][38][39][40][41][42][43][44] Depression: Globally, the total number of people living with depression was estimated to exceed 300 million in 2015, equivalent to 4.4% of the world's population. This estimation increased by 18.4% between 2005 and 2015.…”
Section: Specified Areas Of Preventive Carementioning
confidence: 99%
“…The association between hypothyroidism and hyperuricemia (an important risk factor for the development of gout) has been firmly established. [35][36][37][38][39][40][41][42][43][44] Depression: Globally, the total number of people living with depression was estimated to exceed 300 million in 2015, equivalent to 4.4% of the world's population. This estimation increased by 18.4% between 2005 and 2015.…”
Section: Specified Areas Of Preventive Carementioning
confidence: 99%
“…The literature search initially yielded 955 abstracts, and 46 studies were assessed for eligibility by reading full texts. Thirty-two stud-ies were excluded and 14 studies meeting the inclusion criteria were considered eligible [21][22][23][24][25][26][27][28][29][39][40][41][42]. ▶ table 3 showed the characteristics of those 14 included studies.…”
Section: Meta-analysismentioning
confidence: 99%
“…There were 7 cross-sectional studies, 6 case-control studies and one cohort study. There were 9 studies assessing the impact of gout on hypothyroidism risk [21-24, 26, 39, 41, 42], 4 studies assessing the impact of gout on hyperthyroidism [23,24,26], 8 studies assessing the impact of hyperuricemia on hypothyroidism risk [23, 25, 27-29, 40, 41], and 6 studies assessing the impact of hyperuricemia on hyperthyroidism risk [23,25,27,29,40] (▶ table 3). Based on the NOS criteria, 12 studies had good quality, but the other 2 studies had suboptimal quality.…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a few prior studies have suggested a relationship between gout and thyroid abnormalities, with a few conflicting results [ 10 ]. Thyroid cancer is associated with benign thyroid diseases, including hyperthyroidism, thyroiditis, and autoimmune thyroid diseases [ 11 ]. In addition, both thyroid cancer and gout are associated with metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%